The Effect of Imagery MRA Training on Free Throw Shoot at Players KU-14 (Media Ilmu Keolahragaan Indonesia, 2023)
Abstract. This study had difficulties in shooting, therefore the researchers provided training using imagery training. The purpose of this study was to perform Imagery MRA exercises, with the aim of increasing concentration, increasing self-confidence, controlling emotional responses, improving training skills in shooting basketball free throws. This type of research uses an experimental with a quantitative approach and the one group pretest-posttest design. The population is 15 athletes, and the sample is 15 athletes using total sampling technique. instrument test with free throw test. Data analysis techniques used the normality test, homogeneity test and Wilcoxon test with SPSS IBM 21. The pretest data results were 13.67 and the posttest was 17.33. The pretest standard deviation was 1.91 and the posttest standard deviation was 2.06. The pretest variant value was 3.67 and the posttest was 4.24. The normality test for the pretest L. Count = 0.930 while the posttest L. Table = 0.220 and it is stated that the data is not normally distributed data with a degree of confidence or Sig. of 0.05. L. Count = 0.930 L. Table = 0.220 stated that the data is not normally distributed data with a degree of confidence or Sig of 0.05. Wilcoxon test, it is known that the value of Wcount = 0.00 and Wtable = 25 and it can be concluded that if Wcount = 0.00 Wtable = 25, then H1 is accepted and H0 is rejectedKey words: basketball, free throw, imagery MRAAbstract in Indonesia. Penelitian ini kesulitan dalam melakukan shooting, maka dari itu peneliti memberikan latihan menggunakan imagery training. Tujuan penelitian ini untuk melakukan latihan Imagery MRA, dengan tujuan Meningkatkan konsentrasi, Meningkatkan rasa percaya diri, Mengendalikan respond emosional, Memperbaiki latihan keterampilan dalam melakukan tembakan free throw Basket. Jenis penelitian ini menggunakan eksperimental dengan pendekatan kuantitatif dan desaign the one group pretest-posttest design. Populasi sebanyak 15 atlet dan sampel berjumlah 15 atlet menggunakan teknik  total sampling. instrument tes dengan freethrow test. teknik analisis data menggunakan uji normalitas, uji homogenitas dan uji wilcoxon dengan SPSS IBM 21. hasil data pretest adalah 13,67 dan posttest adalah 17,33. Simpangan baku pretest adalah 1,91 dan simpangan baku posttest adalah 2,06. Nilai varian pretest adalah 3,67 dan posttest adalah 4,24. Uji normalias pretest L.Hitung = 0,930 sedangkan posttest L.Tabel = 0,220 dan dinyatakan data tersebut merupakan data yang terdistribusi tidak normal dengan derajat kepercayaan atau Sig. sebesar 0,05. L.Hitung = 0,930 L.Tabel = 0,220 dinyatakan data tersebut merupakan data yang terdistribusi tidak normal dengan derajat kepercayaan atau Sig sebesar 0,05. uji Wilcoxon, diketahui nilai Whitung = 0,00 dan Wtabel =25 dan dapat di simpulkan jika Whitung = 0,00 Wtabel = 25, maka H1 diterima dan H0 ditolak.